Racism in social media: A Critical Discourse Analysis of YouTube Comments - Shafa Shafa (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Social media plays a role in forming a digital public space that can accommodate all groups, classes, races, or groups to communicate freely, without boundaries, and opens up greater opportunities to reach more interests such as political, economic, cultural, religious, and ethnic. This study explores fundamental difficulties in researching social media texts from a discourse analytic viewpoint. It gives a rationale and framework for analyzing social media conversation based on Critical Discourse Analysis. The study aims to understand how individuals use racism to express themselves on YouTube, one of the most popular websites. The research aimed to determine (1) the types of racism used in YouTube comments and (2) what racism as critical discourses implies. The observation led to the selection of four racist remarks from a YouTube video, which were subsequently evaluated in three phases: textual analysis (description), processing analysis (interpretation), and social analysis (explanation). YouTube comments contain every racist speech outlined by Neubeck and Glasberg (Personal and Institutional racism).